INISIASI ASI TERHADAP MOTORIK BAYI DI RW 08 DUSUN LEBAKJATI DESA CILELES KECAMATAN JATINANGOR - In-In Hanidah; Indira Lanti; Wendry Setiyadi Putranto (Dharmakarya, 2018)
The purpose of this study was to see the initiation habits of breastfeeding and the effect of breast milk on infant. This research is a descriptive qualitative study with subjects of mothers and infant aged 0-24 months. The data collection technique used is observation by observing infant reflexes, and using interview techniques to gather information through asking face-to-face. The analysis technique used is to describe the data obtained in the field. Based on the results of the analysis, it was concluded that infant who get breast milk from their mothers in full from the age of 0-24 months produce good infant reflexes and can carry out activities that are balanced with the development of their age.